2017
DOI: 10.1634/theoncologist.2016-0276
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cancer in the Older Age Person: An Approach to Complex Medical Decisions

Abstract: The management of cancer in older aged people is becoming a common problem due to the aging of the population. There are many variables determining the complex situation that are interconnected. Some of them can be assessed, such as risk of mortality and risk of treatment complications, but many others are still unknown, such as the course of disease, the host-related factors that influence cancer aggressiveness, and the phenotype heralding risk of permanent treatment-related damage.This article presents a dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…Despite this does not completely explain the tendency for clinicians to treat younger patients more intensively, cancer treatments, especially clinical trials, have been less conducted to this specific frailty population [2627]. Recent studies emphasize the importance of geriatric assessment to ensure the most adapted therapies in elderly patients [2428]. The GINECO and others have suggested that systemic treatments should be based not only on initial clinical evaluation, but also on geriatric assessment to reduce morbidity and toxic mortality and to improve OS [2930].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this does not completely explain the tendency for clinicians to treat younger patients more intensively, cancer treatments, especially clinical trials, have been less conducted to this specific frailty population [2627]. Recent studies emphasize the importance of geriatric assessment to ensure the most adapted therapies in elderly patients [2428]. The GINECO and others have suggested that systemic treatments should be based not only on initial clinical evaluation, but also on geriatric assessment to reduce morbidity and toxic mortality and to improve OS [2930].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these complexities, specific focus and attention is drawn to the physical and functional assessment and supportive care needs of the geriatric oncologic population. 10 Targeted approaches are recommended to improve assessment, intervention, and follow up care specific to the needs of this population. 11,12 A large part of the standard of care approaches for cancer disease management and cancer treatment side effect attenuation relies on pharmacological interventions.…”
Section: Geriatric Oncologymentioning
confidence: 99%
“…To structure medical decisions in face of uncertainty, information needs to be translated into clinically relevant knowledge and this is the exact advantage that CGA omics data offer, especially if coupled to user-friendly informatics. Recently, clinical cases have served as paradigms to show the interoperability of an algorithm for optimum decision-making in elderly patients with cancer, focusing on the assessment of (i) cancer-free life expectancy, (ii) cancer-related risks on patient survival, function, or quality of life, and (iii) treatment-related risks and benefits [ 54 ]. Notably and as it has been recently showed by a systematic review of systematic reviews with a focus on the use of CGA tools to predict adverse postoperative outcomes [ 55 ], different clinical settings present a range of demands and needs, when daily clinical practice is taken into account.…”
Section: From Precision Oncology To Geriatric Oncology (Oncogeriatmentioning
confidence: 99%